2022
DOI: 10.1101/2022.01.04.21268536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence, characteristics, and predictors of Long COVID among diagnosed cases of COVID-19

Abstract: Background: Long COVID or long-term complication after COVID-19 has the ability to affect health and quality of life. Knowledge about the burden and predictors could aid in their prevention and management. Most of the studies are from high-income countries and focus on severe cases. We did this study to estimate the prevalence and identify the characteristics and predictors of Long COVID among our patients. Methodology: We recruited adult (≥18 years) patients who were diagnosed as Reverse Transcription Polyme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 23 publications
(19 reference statements)
2
33
1
2
Order By: Relevance
“…Fatigue was the most common symptoms reported in several studies (Mandal et al, 2021) (Arjun et al, 2022). It was confirmed by this study; nearly 60% of patients had fatigue.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Fatigue was the most common symptoms reported in several studies (Mandal et al, 2021) (Arjun et al, 2022). It was confirmed by this study; nearly 60% of patients had fatigue.…”
Section: Discussionsupporting
confidence: 85%
“…Presence of multiple symptoms and severity of acute illness in terms of oxygen requirement were associated with long COVID in this study as well as other studies (Jones et Corresponding Author: Khin Phyu Pyar al., 2021) (Arjun et al, 2022). It was likely that they might probably have high viral load to have severe symptoms though viral load was not easy to perform in poor resource setting.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study conducted by Arjun et al [ 6 ] recruited 487 participants who tested positive for COVID-19. Participants were surveyed regarding vaccination status and long COVID symptomatology.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, Taquet et al did not find any difference between vaccinated and unvaccinated populations [ 19 ]. Paradoxically, Arjun et al reported worsening symptoms in participants who were completely vaccinated before contracting the coronavirus disease [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, by preventing infection with SARS-CoV-2 (Level 1); secondly, by reducing the severity of the disease in vaccinated but infected individuals (Level 2); and finally, vaccination may benefit people who already have long COVID (Level 3). However, recent observational studies provide contradictory results and contain methodological flaws which preclude firm conclusions on level 2 and 3 vaccine impact (6, 7).…”
Section: Introductionmentioning
confidence: 99%